Phenotypes of Galactosaemia in Infants Screened at Birth. Issue 1 (March 1973) - Kelly, Sally; Desjardins, Lucille; Armerding, Paul; Burns, Jean
Abstract : Five genetic forms of galactosaemia were found in 15 infants identified in a newborn screening programme through a combination of laboratory criteria, involving serial assays of transferase and interpretation of isozyme patterns. The biochemical phenotypes of some infants were ascertained only weeks after birth, when transferase activities had increased from initial levels.